Numerical study of the 1/ν neoclassical transport and Mercier plasma stability in an l=2 torsatron with the centered planar magnetic axis - Kalyuzhnyj, V.N.; Nemov, V.V. (Вопросы атомной науки и техники, 2014)
The 1/ν neoclassical transport and Mercier plasma stability for a magnetic configuration of l=2 torsatron system with the centered planar magnetic axis, which was done by selecting the winding law of the helical coils, formed in the model of the l=2 torsatron Uragan-2M type, are investigated numerically. For calculating the transport coefficients and Mercier stability criterion a technique, based on integration along magnetic field lines in a given stellarator magnetic field (NEO code) is used. The magnetic field of helical windings is calculated by the Biot-Savart law. The transport coefficients are presented in a standard form containing a factor depending on the magnetic field geometry. The obtained results are compared with corresponding results for two variants of torsatron Uragan-2M «standard» configuration